Effectiveness of Local History Module Based on Inquiry to Improve the Learning Achievement of High School Students - Mela Mita Septiana; Nunuk Suryani; Akhmad Arif Musadad (JPP (Jurnal Pendidikan dan Pembelajaran), 2018)
The learning process is a process of communication which means the process of delivering a message from a resourcer to the receiver. Media is the part of the communication process because basically learning is a process of communication. Learning media in the form of a module is a supporting device to improve student’s achievement. This study aims to determine the effectiveness of historical learning by using local history module to improve the student’s achievement in senior high school on the historical material of the struggle to defend freedom. The study population was all social science students of class XII academic year 2015/2016. The research design was the group design of pre-test and post-test. The sampling technique used is cluster random sampling, obtained that class XII of Social Science 1 as an experimental class and class XII of Social Science 4 as the controlled class. The results showed the post-test average value of students’ achievement on an experimental class at 79,64 and 76,78 for the controlled classes. Based on the results of this research, it can be concluded that the application of local history module proved effectively in improving the students achievement.